Design of small tag antenna for embedded RFID tracking system - Koh, Hao Zhe (2023)
A novel miniature Radio Identification (RFID) tag antenna has been proposed for embedded metal tracking applications. It uses the meander and shorting techniques to achieve miniaturization, causing the overall antenna size (30 × 30 × 3.2 mm3 ) to be much smaller than other contemporary tag antennas. The incorporated meandered lines and shorted stubs supply additional inductive reactance to the antenna impedance to cancel the capacitive impedance of the UCode8. Despite its compact size, the tag antenna can generate a strong directional radiation when it is embedded inside a metal, which is hardly achieved by conventional metal tag antennas. Prototypes are fabricated and they are tested in a controlled environment in the anechoic cabinet using industrial standard RFID testing equipment and software tools. It has been found that the proposed tag antenna can generate directional radiation patterns with a realized gain up to 0.337 dB when it is placed on a metal plate embedded in a metal cavity. At resonant frequency of 926 MHz, the impedance matching level is almost 100% with an achievable read distance up to ~18.88 m when the tag antenna is either embedded in metal or tagged on metal surfaces. Measurement results show that, the proposed antenna is highly versatile in tracking applications, as it can be embedded in or on metal without significantly affecting its performance.